Simulation and prediction of land use and land cover change using GIS, remote sensing and CA-Markov model - H.A. Khawaldah; I. Farhan; N.M. Alzboun (Global Journal of Environmental Science and Management)
This study analyzes the characteristics of land use/land cover change in Jordan’s Irbid governorate, 1984–2018, and predicts future land use/land cover for 2030 and 2050 using a cellular automata-Markov model. The results inform planners and decision makers of past and current spatial dynamics of land use/land cover change and predicted urban expansion, for a better understanding and successful planning. Satellite images of Landsat 5-thematic mapper and Landsat 8 operational land imager for the years 1984, 1994, 2004, 2015 and 2018 were used to explore the characteristics of land use/land cover for this study. The results indicate that the built-up area expanded by 386.9% during the study period and predict further expansion by 19.5% and 64.6% from 2015 to 2030 and 2050 respectively. The areas around the central and eastern parts of the governorate are predicted to have significant expansion of the built-up area by these dates, which should be taken into consideration in future plans. Land use/land cover change and urban expansion in Irbid are primarily caused by the high rate of population growth rate as a direct result of receiving large numbers of immigrants from Syria and Palestine in addition to the natural increase of population and other socio-economic changes.